Pengaruh Biaya Penjualan, Biaya Administrasi dan Umum Terhadap Penjualan (Studi pada Perusahaan Property dan Real Estate yang terdaftar di Bursa Efek Indonesia periode 2009-2013) - Diah Sartikasari; Eka Sariningsih (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2014)
Abstract. Thfrs study is aimed to test the effect of selling cost and general administration cost to selling of property and real estate company listed in Indonesia stock exchange. The analytical method for determining statistical tests with SPSS (Statistical Package for the Social) 16.00 software, with 10 property and real estate company listed in Indonesia stock exchange period of 2009-2013 as sample. The data used is income statements of property and real estate company listed in Indonesia stock exchange (www.idx.co.id). Based on the results of this study concluded that either altogether or in partial test, selling cost and general administration cost had influence to selling